TINJAUAN KETEPATAN PENGKODEAN DIAGNOSA PADA PASIEN RAWAT INAP DI RUMAH SAKIT JANTUNG DIAGRAM - DEPOK - Indah Kristina; Anisah Anggraeni (MEDICORDHIF Jurnal Rekam Medis, 2022)
ABSTRACT The coding of diagnoses for inpatients at the Diagram Heart Hospital is carried out by the Coder, based on the diagnoses written in the Discharge Summary. The purpose of this study is to determine the diagnostic coding procedure, the completeness of the diagnosis writing, the accuracy of the diagnosis coding and the factors that cause the inaccuracy of the diagnostic coding. Quantitative descriptive research method. The sample used was 63 inpatient discharge summaries in May 2020 which were collected randomly. The results obtained, the completeness of the diagnosis writing on the discharge summary was 100% complete, the accuracy of coding diagnosis was 70% correct, and 30% incorrect, the results of the identification of the diagnostic coding procedure. available refer to coding of diagnoses and coding of medical procedures. The cause of the inaccurate diagnosis coding is known from the Coder's power factor because he is not careful and is unable to read the diagnosis by hand. The understanding of the rules that apply in coding diagnoses by the coder is not optimal, supported by educational background that has not reached a minimum of diploma 3 medical records and health information, thus the accuracy of the diagnosis code is supported by coders who have formal education diploma 3 medical records and health information, understanding of diagnostic coding rules, completeness of diagnosis writing, and clarity of diagnosis writing Keywords: Diagnostic Coding Accuracy, discharge summary, inpatients